(untitled) (Research, Society and Development, 2020)
This study aims to present the reform of secondary education under Law No. 13,415 / 2017 with a view to easing the knowledge to meet the new perspective of work, also more flexible. From the discussion of the Work and Education categories, we seek to understand what directions public education in Brazil has been taking. We realize that public education has been forwarding the same given dualistic model of education in modern school design. The methodological procedures will be conducted using the dialectical materialistic historical method with literature review and documentary analysis. Thus, our hypothesis is that education for the worker aligns the new precarious working format. Thus, we conclude that education, is based on a more flexible model that meets the immediate interests of the market as it relates to ICT, therefore, the capital.